2011
DOI: 10.1002/marc.201100378
|View full text |Cite
|
Sign up to set email alerts
|

Bergman Cyclization in Polymer Chemistry and Material Science

Abstract: Bergman cyclization of enediynes, regarded as a promising strategy for anticancer drugs, now finds its own niche in the area of polymer chemistry and material science. The highly reactive aromatic diradicals generated from Bergman cyclization can undergo polymerization acting as either monomers or initiators of other vinyl monomers. The former, namely homopolymerization, leads to polyphenylenes and polynaphthalenes with excellent thermal stability, good solubility, and processability. The many remarkable prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 46 publications
0
28
0
Order By: Relevance
“…Taking advantage of the designable structure of enediynes, it is very easy to modulate the reaction conditions and variegate the structure, performance, and application of the conjugated polymers. Although still in its infancy, the Bergman cyclization has already appeared as a valuable tool in polymer chemistry where it is applied in a twofold way: (1) the highly reactive p-benzynes generated by the Bergman cyclization can undergo homo-polymerization acting as symmetrical bifunctional monomers; (2) the highly reactive radicals at the chain ends of the conjugated polymers can also be used to covalently modify carbon materials to improve their solubility in organic solvents [3,28].…”
Section: Synthesis Of Linear Conjugated Polymers (1d)mentioning
confidence: 99%
See 2 more Smart Citations
“…Taking advantage of the designable structure of enediynes, it is very easy to modulate the reaction conditions and variegate the structure, performance, and application of the conjugated polymers. Although still in its infancy, the Bergman cyclization has already appeared as a valuable tool in polymer chemistry where it is applied in a twofold way: (1) the highly reactive p-benzynes generated by the Bergman cyclization can undergo homo-polymerization acting as symmetrical bifunctional monomers; (2) the highly reactive radicals at the chain ends of the conjugated polymers can also be used to covalently modify carbon materials to improve their solubility in organic solvents [3,28].…”
Section: Synthesis Of Linear Conjugated Polymers (1d)mentioning
confidence: 99%
“…They found that cis-1,5-hexadiyn-3-ene underwent an exclusively thermal rearrangement to generate a 1,4-didehydrobenzene intermediate which could easily be trapped by external reagents to yield benzene derivatives (Scheme 1) [3]. However, Bergman's research did not receive much attention until the late 1980s when the enediyne-type core structures of many naturally occurring antibiotics, such as calicheamicin [4,5], dynemicin A [6], esperamicin A 1 [7,8] and kedarcidin chromophore [9] were reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the cytotoxicity of the biradical intermediate, it is widely used in pharmaceutical research and organic synthesis [71]. Since 1994, when Tour et al [72] described a radical polymerization route to obtain poly(p-phenylene)s and polynaphthalenes, diradicals from Bergman cyclization have been regarded as very promising and attractive monomers for preparing conjugated aromatic polymers and carbon-rich materials without transition-metal catalysts (Scheme 18) [73].…”
Section: Bergman Reactionmentioning
confidence: 99%
“…12,[14][15][16] Moreover, the photophysical properties of polycyclic aromatic hydrocarbons containing the 5-membered ring are unusual compared to the analogous molecules with 6-membered rings. 3,[5][6][7][8][9][10][11][12][13]15 It is thus of interest to develop a better understanding of the structure-property relationships of the 5-membered ring containing polycyclic aromatic hydrocarbons.…”
mentioning
confidence: 98%